Point-of-Care diagnostic of SARS-CoV-2: knowledge, attitudes, and perceptions (KAP) of medical workforce in Italy - Riccò, Matteo; Ferraro, Pietro; Gualerzi, Giovanni; Ranzieri, Silvia; Bragazzi, Nicola Luigi; Balzarini, Federica; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
Introduction. The present study aims to characterize knowledge, attitudes and beliefs in a sample of medical professionals towards point-of-care (POC) rapid tests for SARS-CoV-2 in Italy (April 2020). Material and Methods. A total of 561 professionals (42.6% males, 26.9% ≥ 50-year-old) compiled a specifically designed web questionnaire on characteristics of POC rapid tests. They were asked whether they would change daily practice and make clinical decisions according to POC tests. Multivariate odds ratios (aOR) for predictors of propensity towards the aforementioned behavioral outcomes were calculated through regression analysis. Results. Overall, only 51.9% knew the official recommendations of the Italian Health Authorities for POC tests, while 26.0% of respondents considered POC tests for COVID-19 highly reliable. Still, 40.3% of respondents would change daily practice because of such tests, and 38.5% would make clinical decisions based of their results. Actual understanding of specificity and sensitivity of POC tests was not associated with assessed behavioral outcomes: main positive effectors were identified in perceived reliability and usefulness of rapid tests, acknowledging the existence of official recommendations, understanding the limited clinical implications of POC tests, and working as occupational physicians were characterized as negative effectors.  Conclusions. Propensity of sampled professionals towards POC tests for COVID-19 was diffusely unsatisfying. While actual understanding of accuracy of such tests was not a main effector of propensity, previous experiences with other POC tests in daily practice, particularly among occupational physicians may have impaired overall acceptance of such instruments.